2006
DOI: 10.1007/s00415-006-1103-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychology of multiple sclerosis

Abstract: Neuropsychological dysfunctions have been well documented in patients with multiple sclerosis. We herein give an overview of the main findings of recent decades. The pros and cons of considering the cognitive deficits of multiple sclerosis patients as a form of 'subcortical dementia' are discussed. By comparing the neuropsychological descriptions of multiple sclerosis patients as given in the literature to other neurological diseases which are also associated with neuropsychological deficiencies, we propose th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(97 citation statements)
references
References 53 publications
2
88
0
7
Order By: Relevance
“…Approximately two thirds of patients experience cognitive problems (Rao et al, 1993;Amato, Zipoli, & Portaccio, 2006). These include deficits in memory, attention, and executive functions (Calabrese, 2006;Chiaravalotti & DeLuca, 2008), which cause difficulties in engaging in rehabilitation, maintaining employment, and participating in social activities. A national survey of people with MS found that cognitive problems were perceived to be the most debilitating aspect of MS and a source of distress for those affected and their families and carers (Dorning, Luck, & Holloway, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately two thirds of patients experience cognitive problems (Rao et al, 1993;Amato, Zipoli, & Portaccio, 2006). These include deficits in memory, attention, and executive functions (Calabrese, 2006;Chiaravalotti & DeLuca, 2008), which cause difficulties in engaging in rehabilitation, maintaining employment, and participating in social activities. A national survey of people with MS found that cognitive problems were perceived to be the most debilitating aspect of MS and a source of distress for those affected and their families and carers (Dorning, Luck, & Holloway, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive dysfunction in MS involves several domains including information processing speed, attention, memory and frontal executive functions [7]. This heterogeneity is usually not observed in individuals with CIS, in whom only deficits of information processing speed and working memory have been described [5].…”
mentioning
confidence: 99%
“…Information processing speed, verbal memory, cognitive flexibility and executive function are all impaired. 39 The presentation of cognitive deficit in MS is variable. Cognitive function tends not to correlate with other markers of relapse and remission and the syndrome of a rapidly progressive dementia is rare but there is usually a progressive course with more cognitive domains affected, as well as correlation with markers of physical disability and social dysfunction.…”
Section: Cognitive Disordersmentioning
confidence: 99%